Uncovering the mechanisms underlying the efficacy of probiotic strains in mitigating food allergies: an emphasis on gut microbiota and indoleacrylic acid - Pei, Zhangming; Qian, Li; Miao, Taolin; Wang, Hongchao; Lu, Wenwei; Chen, Yuqing; Zhuang, Qianger (Frontiers in Nutrition, 2024)
Food allergies manifest as systemic or digestive allergic responses induced by food allergens, and their progression has been demonstrated to be intimately associated with the host's gut microbiota. Our preceding investigation has revealed that the probiotic strains Lactiplantibacillus plantarum CCFM1189 and Limosilactobacillus reuteri CCFM1190 possess the capability to mitigate the symptoms of food allergy in mice. However, the underlying mechanisms and material foundations through which these probiotic strains exert their effects remain enigmatic. Here, we initially compared the ameliorative effects of these two probiotic strains on food allergy mice subjected to antibiotic cocktail (ABX) treatment. It is indicated that ABX treatment was ineffective in alleviating weight loss, diarrhea, and allergic symptoms in mice, and it also inhibited the reduction of histamine and T helper cell 2 (Th2) cytokines mediated by effective strains, suggesting that effective strains must operate through the gut microbiota. Then, building upon the outcomes of prior nontargeted metabolomics studies, by quantifying the content of indoleacrylic acid (IA) in single-strain fermentation of probiotic strains and mouse feces, it was ascertained that effective strains do not synthesize IA themselves but can augment the concentration of IA in the gut by modulating the gut microbiota. Ultimately, we discovered that direct intervention with IA could mitigate diarrhea, allergic symptoms, and intestinal damage by modulating immunoglobulin E (IgE) levels, histamine, Th2 cytokines, and tight junction proteins, thereby corroborating that IA is a pivotal metabolite for the alleviation of food allergies. These observations underscore the significance of gut microbiota and metabolites like IA in the management of food allergies and hold potential implications for the 35 development of novel therapeutic strategies.